Feasibility of using latex examination gloves as dental dam: a tensile strength study / Budi Aslinie Md Sabri … [et al.] - Md Sabri, Budi Aslinie (Faculty of Dentistry, 2015)
Objective: To evaluate feasibility of hand gloves as a rubber dam isolation alternative, in respect of physical properties. Materials and Methods: A randomized controlled trial study design was used. Three types of gloves were tested with two types of a rubber dam used as the control group. Cut-out pattern of dumb-bell shapes were made from 35 samples for each type of groups and tensile strength were tested using Universal Testing Machine and the Trapezium X software. All tests for physical requirements were performed in accordance with American Society for Testing and Materials D412, Standard Test Methods for Vulcanized Rubber and Thermoplastic Rubbers and Thermoplastic Elastomers-Tension. Findings were analyzed by analysis of variance (ANOVA) and differences were compared using a Tukey-Kramer interval calculated at the 0.05 significance level. Results: Heavy gauge rubber dam has the highest Mean (calculated at the 0.05 significance level) except for maximum stress calculated at entire area. Medium-gauge rubber dam has significantly higher tensile strength (44.5075 N/mm²) when compared to heavy-gauge rubber dam (35.7787 N/mm²) although it was 0.09mm thinner. Discovery 2020 Powder Free Latex Examination Gloves with tensile strength value of 28.5922 N/mm² (±3.27366) is more than the minimum requirement specified by American Federal Specification ZZ-R90B Rubber Dam (Dental, 1985) (4000 pounds per square inch or 27.6 N/mm²). For all variable tested, all groups are significantly different from each other. The mean square between the groups was quite large. Conclusion: This study shows that there are significant differences between the physical strength of latex gloves when compared to rubber dam. However, the comparison between thickness and tensile strength among various rubber dam, did not correspond proportionately. Only one type of rubber gloves met the minimum requirement but that is just one aspect. In view of these mixed results, more research is needed before we can conclude that it is feasable that we use hand gloves to replace rubber dam.